P.029 Oral Daily Atogepant for the Preventive Treatment of Migraine Increases Responder Rates for Reduction in Mean Monthly Migraine Days. (November 2021) - Lipton, RB; Pozo-Rosich, P; Blumenfeld, AM; Dodick, DW; McAllister, P; Li, Y; Lu, K; Dabruzzo, B; Davidovic, G; Miceli, R; Severt, L; Finnegan, M; et al.
Abstract : Background: The goal of the study was to assess responder rates at various times after initiating atogepant treatment. Methods: A 12-week phase 3 trial evaluated the safety, efficacy, and tolerability of atogepant for preventive treatment of migraine (ADVANCE; NCT03777059) in adult participants with a ≥1-year history of migraine, experiencing 4-14 migraine days/month. Participants were randomized to atogepant 10, 30, or 60mg, or placebo once daily. These analyses evaluated ≥25%, ≥50%, ≥75%, and 100% reductions in mean monthly migraine days (MMDs) across 12 weeks and each 4-week interval. Adverse events (AEs) in ≥5% of participants are reported. Results: The efficacy analysis population included 873 participants: placebo: n=214; atogepant: 10mg: n=214; 30mg: n=223; 60mg: n=222. Atogepant-treated participants were more likely to experience a ≥50% reduction in the 3-month mean MMDs (56-61% vs 29% with placebo; P <0.0001). The proportions of participants experiencing ≥25%, ≥50%, ≥75%, and 100% reductions in mean MMDs significantly increased during each 4-week interval (≥50% reduction: 48-71% vs 27-47% with placebo). The most common AEs for atogepant were constipation (6.9-7.7%) and nausea (4.4-6.1%). Conclusions: Once-daily atogepant 10, 30, and 60mg significantly increased responder rates at all thresholds with approximately 60% achieving a ≥50% reduction in mean MMDs at 12 weeks.